The role of Ca2+/calmodulin-dependent protein kinase II and calcineurin in TNF-α-induced myocardial hypertrophy - Gui-Jun Wang; Hong-Xin Wang; Yu-Sheng Yao; Lian-Yi Guo; Pei Liu (Brazilian Journal of Medical and Biological Research, 2012)
We investigated whether Ca2+/calmodulin-dependent kinase II (CaMKII) and calcineurin (CaN) are involved in myocardial hypertrophy induced by tumor necrosis factor α (TNF-α). The cardiomyocytes of neonatal Wistar rats (1-2 days old) were cultured and stimulated by TNF-α (100 μg/L), and Ca2+ signal transduction was blocked by several antagonists, including BAPTA (4 µM), KN-93 (0.2 µM) and cyclosporin A (CsA, 0.2 µM). Protein content, protein synthesis, cardiomyocyte volumes, [Ca2+]i transients, CaMKIIδB and CaN were evaluated by the Lowry method, [³H]-leucine incorporation, a computerized image analysis system, a Till imaging system, and Western blot analysis, respectively. TNF-α induced a significant increase in protein content in a dose-dependent manner from 10 µg/L (53.56 µg protein/well) to 100 μg/L (72.18 µg protein/well), and in a time-dependent manner from 12 h (37.42 µg protein/well) to 72 h (42.81 µg protein/well). TNF-α (100 μg/L) significantly increased the amplitude of spontaneous [Ca2+]i transients, the total protein content, cell size, and [³H]-leucine incorporation in cultured cardiomyocytes, which was abolished by 4 µM BAPTA, an intracellular Ca2+ chelator. The increases in protein content, cell size and [³H]-leucine incorporation were abolished by 0.2 µM KN-93 or 0.2 µM CsA. TNF-α increased the expression of CaMKIIδB by 35.21% and that of CaN by 22.22% compared to control. These effects were abolished by 4 µM BAPTA, which itself had no effect. These results suggest that TNF-α induces increases in [Ca2+]i, CaMKIIδB and CaN and promotes cardiac hypertrophy. Therefore, we hypothesize that the Ca2+/CaMKII- and CaN-dependent signaling pathways are involved in myocardial hypertrophy induced by TNF-α.